Commercialisation of kinship in an urban setting - Nyoni, Phefumula Nyaningwe (My University, 2017)
This research is an investigation of how kinship is mobilised for commercial purposes by business persons and with what kinds of effects on forms of kinship and obligation. Ntabankulu urban, located in the Eastern Cape Province of South Africa has specifically been targeted for this purpose. Through in-depth interviews targeting ‘Black’ South African business owners, the research establishes the identities of the business persons whilst further exploring how they draw from non-capitalist forms of organisation such as kinship in dealing with various challenges associated with the dictates of capitalist enterprise. Important is the point that the black business persons involved in this study have emerged from what can be deemed as ‘liminal’ precarious socio-economic backgrounds and proved to be active agents who could successfully draw from practices based on non-capitalist forms of organisation such as kinship to deal with obligation-related challenges encountered within an inherently capitalist context. This study constitutes a break from conventional economics that has previously viewed customary elements such as kinship as detrimental to business. This break is represented by noting the resilience of non-capitalist forms of organisation, particularly within the business context. Besides that, the relationship between culture and the market has been repositioned to create a close relational situation in contrast to previous claims of the two being incompatible. The study explores the ideas of kinship and related practices, reciprocal cooperation and conflict as well as modernity’s influences within the context of efforts aimed at balancing kinship with business obligations. In addition, the study investigates how the inevitable coexistence of customary and business practices leads to newly invented forms of organisation that have seen ethnic communities notably reinventing themselves into business entities. It follows that South African corporations, just as is the case the world over, are increasingly embracing customary values such as kinship in efforts to explore alternative markets and structures of consumption. The study also assesses the complexities involved in balancing kin and business obligations especially in relation to the multiplicity of kin and business obligations that in instances tend to be contradictory.
A thesis submitted to the Faculty of Humanities in fulfilment of the requirements for the degree of Doctor of Philosophy, March 2017.
Keywords: Kinship--South Africa; Social structure--South Africa; Business anthropology--South Africa